CRAFTSWOMEN IN MEDIEVAL SERBIA: A COMPARATIVE VIEW - ALEKSANDRA FOSTIKOV (Истраживања)
As a research topic, women in medieval Serbian lands who were engaged professionally in skilled crafts is practically unexplored territory. In addition to a chronic lack of sources—which is clearly evident in the case of women’s work in producing commodities—exploration of the role of women’s work, even in medieval society, did not begin until the emergence of historiography of sex and gender, in particular at the end of the twentieth century. In addition to women from the ruling and aristocratic classes, who were noticeably preserved in the surviving sources in accordance with their status, the documents, primarily from the interior, mostly record widows due to their specific position in society, with the exception of a few legal provisions regulating women’s earnings. Narrative sources predominantly created within the Church view women through a Christian perspective and omit women’s work. However, information preserved in coastal cities such as Kotor or Dubrovnik, cities in the interior in neighboring states of what was previously Serbia and throughout medieval Europe, allow for parallels to be drawn and for issues related to the work of skilled craftswomen to be better understood. Through the comparative method based on currently established methodology, this paper will present women’s activities as professional craftswomen, their work as assistants in workshops, and their activities related to the infrastructure of a particular craft so that what is already known can be interpreted using source material and literature of both local and foreign origin in order to determine at least an approximate framework and role for women within the skilled crafts in medieval Serbia.